Malaria in pregnancy in India: a 50-year bird’s eye - Kojom Foko, Loick Pradel; Singh, Vineeta (Frontiers in Public Health, 2023)
In 2021, India contributed for 79% of malaria cases and 83% of deaths in the South East Asia region. Here, we systematically and critically analyzed data published on malaria in pregnancy (MiP) in India.Methods: Epidemiological, clinical, parasitological, preventive and therapeutic aspects of MiP and its consequences on both mother and child were reviewed and critically analyzed. Knowledge gaps and solution ways are also presented and discussed. Several electronic databases including Google scholar, Google, PubMed, Scopus, Wiley Online library, the Malaria in Pregnancy Consortium library, the World Malaria Report, The WHO regional websites, and ClinicalTrials.gov were used to identify articles dealing with MiP in India. The archives of local scientific associations/journals and website of national programmes were also consulted.Results: MiP is mainly due to Plasmodium falciparum (Pf) and P. vivax (Pv), and on rare occasions to P. ovale spp and P. malariae too. The overall prevalence of MiP is 0.1 -57.7% for peripheral malaria and 0 -29.3% for placental malaria. Peripheral Pf infection at antenatal care (ANC) visits decreased from 13% in